Fidelity of a simple Liberty leaf-painting assay to validate transgenic maize plants expressing the selectable marker gene, bar. Issue 4 (4th July 2017) - Rajasekaran, K.; Majumdar, R.; Sickler, C.; Wei, Q.; Cary, J.; Bhatnagar, D.
ABSTRACT: Screening of gene manipulation events (transgenic, mutation/genome editing, etc.) is a cost/labor-intensive and time-consuming process in plant science research. While polymerase chain reaction (PCR) is the most commonly used method for screening, the process still requires efficient DNA extraction and subsequent confirmation. However, PCR cannot predict gene expression. To screen a larger number of transgenic plants, it would be ideal to develop a quick and reliable screening procedure. We have applied a Liberty ® leaf-painting method (against bar gene under 4x35S promoter) to screen transgenic maize ( Zea mays L.) plants and validated the results through PCR and quantitative real-time PCR (qRT-PCR). Liberty leaf painting at 500 mg L −1 a.i. was > 95% accurate in identifying transgenic events that agreed with the PCR results. Further investigation of bar gene expression in sensitive lines that were PCR positive shows very low expression of the bar gene. We have provided a simple, and rapid assay to determine the transgene expression potential of maize plants expressing the bar gene. The herbicide can be applied to a fully expanded leaf and evaluated one week after application. Green or partially green leaf blades indicate high or moderately high expression of the bar gene and a total yellowing indicates absence or extremely low expression of the bar gene in the transgenic plants. A small volume of Liberty solution is adequate to test hundreds of maize plants, and the assay is reproducible with a high frequency (> 95%) and also displays good correlation with gene expression in planta .